The impact of maternal diabetes on the future health and neurodevelopment of the offspring: a review of the evidence - Rodolaki, Kalliopi; Pergialiotis, Vasilios; Iakovidou, Nikoleta; Boutsikou, Theodora; Iliodromiti, Zoe; Kanaka-Gantenbein, Christina (Frontiers in Endocrinology, 2023)
Maternal health during gestational period is undoubtedly critical in shaping optimal fetal development and future health of the offspring. Gestational diabetes mellitus is a metabolic disorder occurring in pregnancy with an alarming increasing incidence worldwide during recent years.Over, the years ,there is a growing body of evidence that uncontrolled maternal hyperglycaemia during pregnancy can potentially have detrimental effect on the neurodevelopment of the offspring. Both human and animal data have linked maternal diabetes with motor and cognitive impairment, as well as autism spectrum disorders, attention deficit hyperactivity disorder , learning abilities and psychiatric disorders. This review presents the available data from current literature investigating the relationship between maternal diabetes and offspring neurodevelopmental impairment. Moreover, possible mechanisms accounting for the detrimental effects of maternal diabetes on fetal brain like fetal neuroinflammation , iron deficiency, epigenetic alterations, disordered lipid metabolism and structural brain abnormalities are also highlighted . On the basis of the evidence demonstrated in the literature, it is mandatory that hyperglycaemia during pregnancy will be optimally controlled and the impact of maternal diabetes on offspring neurodevelopment will be more thoroughly investigated .